Lost and Found? Jewish Historians, Jewish History, and Narrativization of Order in East European Cities. Issue 1 (24th April 2017) - Ury, Scott
Abstract : This article argues that the long-standing turn to "the Jewish community" as a central organizing principle in works dedicated to Jewish history in east European cities has helped create and institutionalize a specific communal model of Jewish urban history, one that prioritizes narratives of Jewish communal order over explorations of the chaos and fluidity that characterize many other studies of the modern city. The article begins by discussing the central place of "the community" in foundational works of Jewish history, continues by examining the critical role played by communal record books ( pinkasim ) in the construction of east European Jewish history, and then analyzes several works that embraced and reinforced the communal model of Jewish urban history. The article concludes by examining two key archival collections and discussing the various ways that the source material amassed in them illustrates how scholars like Jacob Shatzky and Israel Klausner used historical research and writing as a means to narrativize, domesticate, and make sense of the intersection between Jews and cities.